Exploring The Need For Developing An English Workbook Integrating Madurese Culture In Elementary School - Izzah Fijriyah; Andika Adinanda (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The purpose of this research is to ascertain the needs students have about English workbooks that incorporate Madurese culture in order to teach English to elementary school students. The survey method was employed in this study. Interviews and student needs surveys were employed as data gathering tools. Twenty Elementary School children in the first semester of SDN Paseyan 1 Sampang Madura, particularly in the academic year 2025/2026, and an English teacher became research subjects. The interview results were evaluated descriptively, while the questionnaires were assessed based on percentages. The questionnaire includes questions about Madurese culture-based learning, English-language instruction in schools, and literature used in the classroom. The findings reveal that the majority of SDN Paseyan 1 Sampang students agreed that English workbook incorporating Madurese culture is needed.